A General Equilibrium Analysis of Demand Side Management Programs under the Clean Development Mechanism of the Kyoto Protocol - Timilsina, Govinda R. (World Bank, Washington, DC, 2012)
This paper analyzes the economic and environmental consequences of a potential demand side management program in Thailand using a general equilibrium model. The program considers replacement of less efficient electrical appliances in the household sector with more efficient counterparts. The study further examines changes in the economic and environmental effects of the program if it is implemented under the clean development mechanism of the Kyoto Protocol, which provides carbon subsidies to the program. The study finds that the demand side management program would increase economic welfare if the ratio of unit cost of electricity savings to price of electricity is 0.4 or lower even in the absence of the clean development mechanism. If the program's ratio of unit cost of electricity savings to price of electricity is greater than 0.4, registration of the program under the clean development mechanism would be needed to achieve positive welfare impacts. The level of welfare impacts would, however, depend on the price of carbon credits the program generates. For a given level of welfare impacts, the registration of the demand side management program under the clean development mechanism would increase the volume of emission reductions.